Refleksiv Sports Management – Sports Management i et socio- filosofisk perspektiv - Adamsen, Billy (Forum for Idræt, 2014)
Refleksiv Sports Management – Sports management i et socio-filosofisk perspektiv (Reflexive Sport Management – a socio-philosophical approach to sport management) Sports management and its development is closely linked to the development of modern society and modern rationality. This article applies sociological theories and practical management philosophy to shed light on how sports management and its rationality in Denmark (Europe) and the United States have changed and undergone different phases for more than a century, and to show that, in late modernity, they are entering a new phase in which they seem to be more reflexive and communicative. This trend is evident in American sports management and will also soon be reflected in Danish sports management. My analysis of this development will also be based on a specific case study from the American world of sports, namely the story of Oakland Athletics baseball club’s reorganisation in the 1990s, because it both provides a rare insight into a modern sports organisation and demonstrates the reflexive and communicative dimension in late modern sports management.